Interpreting sacred space: A Peircean semiotic study of symbolic meaning in Al-Safar Mosque (ARTEKS : Jurnal Teknik Arsitektur, 2026)
Semiotics investigates the ways in which meaning is produced, transmitted, and interpreted through signs related to form, movement, and human perception. Within the architectural domain, elements such as form, light, materiality, and spatial orientation function as communicative signs that articulate philosophical, symbolic, and spiritual values. This study seeks to interpret the sacred meanings embedded within both the architectural form and the lived spatial experience of the Al-Safar Mosque by employing Charles Sanders Peirce’s semiotic framework, which consists of the triadic relationship between Representamen, Object, and Interpretant. A descriptive qualitative research approach was adopted, integrating Peircean semiotic analysis with the interpretative research design proposed by Creswell & Poth (2024). This methodological framework was supported by systematic field observations, in-depth interviews, and comprehensive architectural documentation. The analysis of spatial experience was structured through five sequential spatial nodes: Approach (niyyah), Threshold (takhalli), Ablution (tazkiyah), Prayer (taw??d), and Exit (tajall?), each representing a distinct phase of bodily movement and spiritual transition. The findings demonstrate that architectural form, lighting conditions, material expression, and spatial direction operate as interconnected semiotic signs that collectively guide physical movement while simultaneously facilitating spiritual contemplation. These elements work synergistically to shape an embodied experience in which architectural space becomes an active medium of meaning. The study concludes that the Al-Safar Mosque conveys sacred meaning through an integrated and embodied spatial experience, thereby contributing to the advancement of architectural semiotics by positioning movement itself as a meaningful language of worship.